Efficacy of 4 weeks topical bifonazole treatment for onychomycosis after nail ablation with 40% urea: a double‐blind, randomized, placebo‐controlled multicenter study. Issue 4 (16th April 2013) - Tietz, Hans‐Jürgen; Hay, Roderick; Querner, Susanne; Delcker, Andreas; Kurka, Peter; Merk, Hans F.
Summary Onychomycosis is a common fungal infection most often affecting the toenails. If untreated, it can cause discomfort sufficient to reduce quality of life. To evaluate efficacy and safety of bifonazole cream vs. placebo in onychomycosis treatment after non‐surgical nail ablation with urea paste. Fifty‐one study centres randomized 692 subjects with mild‐to‐moderate onychomycosis to receive bifonazole 1% cream or placebo for 4 weeks following non‐surgical nail ablation with urea 40% paste over 2–4 weeks. Efficacy of the two phase treatment was evaluated by overall cure of the target nail comprising clinical and mycological cure 2 weeks, 3 and 6 months after end of treatment. At 2 weeks (primary endpoint), overall cure rate was superior in bifonazole‐treated group (54.8% vs. 42.2% for placebo; P = 0.0024). The clinical cure rate was high in both treatment groups (86.6% bifonazole vs. 82.8% placebo), but proportion with mycological cure was higher with bifonazole treatment (64.5%) vs. placebo treatment 49.0%, (P = 0.0001). We observed higher early overall cure rate with 4 weeks topical bifonazole compared with placebo after removal of infected nail parts with urea. This two stage treatment was well tolerated and offers an additional option in topical onychomycosis therapy.